Odpowiedzi

2010-01-21T16:04:05+01:00
A) 3(4,5-1)-2= 8,5
b) 2(0,5+6)-4(0,5-6)=13+22=35
c) 3(-0,5-8)-(5-2(-0,5))= -25,5-4=21,5

myślę że dobrze ;)
4 2 4
2010-01-21T16:04:24+01:00
A)3(x-1)-2 dla x=4,5

=3x -3 -2 =
= 3x -5
= 3*4,5 -5 = 13,5 - 5 = 8,5

b)2(y+6)-4(y-6) dla y=0,5
= 2y +12 -4y + 24=
= -2y + 36

= (-2)*(0,5) + 36 = - 1 + 36 = 35

c)3(a-8)-(5-2a) dla a=-0,5
=3a - 24 - 5 + 2a=
= 5a - 29

5*(-0,5) - 29= - 2,5 -29 = - 31,5
4 5 4
2010-01-21T16:04:28+01:00
A)3(x-1)-2 dla x=4,5
3(4,5-1)-2=13,5-3-2=8,5

b)2(y+6)-4(y-6) dla y=0,5
2(0,5+6)-4(0,5-6)=1-12-2+24=11

c)3(a-8)-(5-2a) dla a=-0,5
3(-0,5-8)-(5-1)=-1,5-24-5+1=-30,5+1=-29,5
4 2 4